Plant NLR-triggered immunity: from receptor activation to downstream signaling. (February 2020) - Lolle, Signe; Stevens, Danielle; Coaker, Gitta
Highlights: Plant NLRs recognize intracellular effectors, inducing cell death and resistance. NLRs exhibit diverse localization and modes of effector recognition. The Arabidopsis ZAR1 NLR forms a pentameric resistosome complex upon activation. Abiotic stress and innate immunity induce overlapping transcriptional reprogramming. Abstract : Innate immune perception is the first line of inducible defense against invading pathogens. Plants lack specialized circulating immune cells. Therefore, diverse cell types are able to recognize and respond to pathogens. Surface-localized and intracellular plant innate immune receptors are capable of recognizing diverse pathogen components. Intracellular nucleotide-binding leucine-rich repeat (NLR) receptors recognize pathogen effectors delivered inside host cells. Recent advances shed light onto NLR activation, phosphorylation of defense signaling nodes and overlap in transcriptional responses between pathogen perception and abiotic stress.